COMPARATIVE ANALYSIS OF KAZAKHSTANI AND EUROPEAN DESIGN SPECIFICATIONS: RAFT FOUNDATION, PILE FOUNDATION, AND PILED RAFT FOUNDATION - Zhanabayeva, Assel; Sagidullina, Nazerke; Kim, Jong; Satyanaga, Alfrendo; Lee, Deuckhang; Moon, Sung-Woo (Applied Sciences, 2021)
The introduction of Eurocode in Kazakhstan allows for the application of modern technological innovations and the elimination of technical barriers for the realization of international projects. It is significant to study the international standards and design requirements provided in Eurocode. This study presents a comparative analysis of Kazakhstani and European approaches for the geotechnical design of foundations and provides the design methods in the considered codes of practice. Three different types of foundations (i.e., raft, pile, and piled raft foundations) were designed following SP RK 5.01-102-2013—Foundations of buildings and structures, SP RK 5.01-103-2013—Pile foundations, and Eurocode 7: Geotechnical design for the Nur-Sultan soil profile. For all three types of foundations, the calculated results of bearing resistance and elastic settlement showed the conservativeness of Eurocode over SNiP-based Kazakhstani building regulations, as the values of bearing resistance and elastic settlement adhering to Kazakhstani code exceeded the Eurocode values. The difference between the obtained results can be explained by the application of higher values of partial safety factors by Eurocode 7. Sensitivity analysis of the bearing resistance on foundation parameters (i.e., raft foundation width and pile length) for the Kazakhstani and European approaches was performed to support the conclusions of the study
Keywords: Type of access: Open Access; raft foundation; pile foundation; piled raft foundation; bearing resistance; elastic settlement